Effectiveness of Peripheral Nerve Block for Early Active Exercise: Three Cases of Pyogenic Flexor Tenosynovitis - Takahiro Sato; Tsuyoshi Shirahata; Koji Nozaka; Naohisa Miyakoshi (Case Reports in Orthopedics)
To prevent limitations in the range of motion after hand surgery, it is crucial to minimize scar tissue formation and adhesions. Thus, it is important to initiate active hand exercises during the early postoperative period. Peripheral nerve blocks (PNBs) may be employed for active hand exercises as they minimize postoperative pain. We reported three cases of pyogenic flexor tendonitis in which PNB was administered postoperatively, and changes in the range of motion were observed. In all cases, a pulp–palmar distance (PPD) of 1 mm was achieved within 1 week after surgery under PNB, and all cases were evaluated as “good” in Flynn’s functional evaluation at the last observation. However, PPD worsened at 3 weeks postoperatively, and all patients exhibited limited proximal interphalangeal joint extension at the final observation. Although our method effectively improved the flexion range of motion, additional measures should be taken to improve the extension range of motion.